Therapeutic Assessment of High-Intensity Focused Ultrasound for Vulvar Lichen Sclerosus by Active Dynamic Thermal Imaging and Hyperspectral Imaging—A Preliminary Study - Qu, Yingjie; Meng, Yuquan; Feng, Sui; Liu, Maoyu; Xiao, Linlin; Zhang, Xiaoyuan; Zheng, Jinjin; Chang, Shufang; Xu, Ronald X. (Frontiers in Physics, 2020)
Vulvar lichen sclerosus (VLS) is a common inflammatory condition associated with an increased risk of developing vulvar carcinoma. Recently, high-intensity focused ultrasound (HIFU) has been identified as a promising treatment modality for VLS in several clinical trials. However, in HIFU therapy, therapeutic outcome is routinely assessed visually by an expert using standardized grading criteria. Furthermore, such a therapeutic assessment cannot be made until at least three months after treatment. Therefore, an objective and timely method capable of quantitatively evaluating HIFU treatment effectiveness is desired, which may help identify patients whose treatment are insufficient in time and prevent the delay of re-treatment. The purpose of this study is to investigate the feasibility of using active dynamic thermal imaging (ADT) and hyperspectral imaging method (HSI) as two individual objective and non-invasive optical methods for quantitative assessment of the therapeutic response of HIFU treatment for VLS, promptly. From December 2018 to March 2019, 20 female patients of VLS, who underwent HIFU treatment, were evaluated using both ADT and HSI methods. Effective damage rate from ADT method and entropy of feature index from HSI method were used to develop a multivariate linear discriminant classification model for grading the effectiveness of HIFU treatment in comparison with clinical evaluation gold standard. Finally, ADT was able to correctly differentiate ineffective treatments from effective ones with a sensitivity of 100% and specificity of 100% while the sensitivity and specificity of HSI were 75% and 87.5%, respectively. The classification results demonstrate the clinical potential of ADT and HSI methods for non-invasive and quantitative assessment of HIFU treatment for VLS in time.